Management of Drills in Swimming for Athletes Ages 6-18 - Nyoman Putra Arya Gunawan; I Made Satyawan; Kadek Yogi Parta Lesmana (Universitas Negeri Semarang, 2026)
The management of drills in swimming for school-age athletes (6-18 years old) requires a very high level of precision with a minimum fault tolerance threshold of up to 1%. This study aims to determine the optimal management of drill exercises to improve the technical performance of athletes in a sustainable manner. The method used is a literature review of 9 relevant sources published between 2020 and 2026. The results of the analysis show four main pillars in the management of drill exercises: (1) integrating the coach's understanding of sport science and biomechanical analysis to objectively identify technical deviations; (2) selection of specific training programs according to the needs of individual athletes; (3) the application of undulating or non-linear periodization which has been shown to be more effective in maintaining performance consistency and preventing neuromuscular saturation in young athletes; and (4) the use of assistive devices such as pull buoys, fins, and buoys, as well as motion analysis technologies (such as Kinovea) to isolate technical weaknesses and improve movement efficiency in the water. Overall, the synergy between data-driven planning, rigorous operational standardization, and continuous evaluation is a key foundation in optimizing long-term swimming performance.